27 CLINICAL SCIENCE RESEARCH PROGRAM: THE MISSING MENTOR?. (1st March 2006) - Hall, D. A.; Efird, M.; Sheeder, J.; Smith, D.; Wells, C.; Box, T.; Shroyer, A. L.
Abstract : Purpose: To fulfill a requirement of the clinical science (CLSC) course "Clinical Outcomes Assessment" at the University of Colorado, participating students in the program designed a survey to evaluate student perceptions related to the Clinical Research Training Program (CRTP) and to identify opportunities for improvement. Methods: The students designed a 99-question series in an on-line Web-based survey using a 5-point Likert scale to evaluate the structures, processes, and outcomes that might be anticipated from any successful NIH K-30 funded program. The survey covered the following domains: (1) self- assessments related to accreditation for GME research-related competencies; (2) course scheduling; (3) support required for manuscript/grant writing; (4) faculty mentorship; and (5) career development goals and planning. Respondents were asked about both the courses taken and their manuscript/grant writing productivity. Summary of Results: Sixty-five (56%) students responded. Results for the five domains included (1) statistically significant improvement in student perceptions related to their self-assessment for competencies from the start of the program to the time of survey; (2) student responses increased from "unsure"/"disagree" toward "agree" for the following constructs: (a) devise/rigorously test experimental hypotheses; (b) relate clinical research to the development of new modalities; (c) comply with ethical standards; (d) successfully conduct a clinical research project; and (e) select/apply the appropriate research method/statistical approach to a given research question. The most striking result, however, was that the CRTP was not successful in coordinating faculty mentor support for student research projects. When a mentorship was documented to exist outside of the program, almost all students were satisfied that their faculty mentoring relationship had successfully met their expectations. Approximately 78% of the student survey respondents noted a lack of satisfaction with the CLSC Program's support to find a primary faculty mentor who met their research project needs and long-term career goals. Conclusions: Overall, the CRTP students indicated the curriculum was successfully meeting their needs. Given that the program currently has over 78 dedicated graduate school faculty, representing a wide diversity of clinical and analytical disciplines, the survey finding that many students were missing a faculty mentorship relationship was unanticipated. Although other NIH funding options for "Mentoring a Mentor" programs exist, the program students recommended that NIH support K-30 programs incorporating this type of mentoring outreach as well as providing fiscal incentives to mentors in the future.